Indicators and Treatment of Dental Caries in Children with Disabilities - Xolova N. F.; Xabibova N. N. (Researchparks Publishing, 2021)
Relevance. The problem of increasing the effectiveness of determining the purpose of dental caries in children with cerebral palsy and improving treatment methods is currently considered as of great importance in maintaining the health of the younger generation, as well as in profiling diseases [2.4.6.8]. Dental diseases are among the most common diseases among other diseases, and caries and its complications occupy a leading place in children with cerebral palsy. Cerebral palsy in children is detected in about 1000 people out of 3-5 babies born. According to the results of dental examinations, the prevalence of dental caries and its complications in children with cerebral palsy ranges from 80% to 85% [1.3.5.7.9]. Therefore, the main attention in the world is paid to the development of new highly effective methods for the prevention of childhood caries. According to the World Health Organization (WHO), the number of severe complications caused by the disease of 3-4 teeth in three-year-olds increases on average. Severe and complex complication of caries is caused by the development of acute and chronic odontogenic inflammatory process in temporary teeth. In the world, there are many endo - and exogenous methods for the prevention of dental caries, on the basis of their application, the newly emerging carious disease was reduced to 30-40% [10.11.13.16]. The organization of an effective system of caries profiling in children is one of the urgent problems facing the employees of the field.